2019
DOI: 10.1002/jts.22441
|View full text |Cite
|
Sign up to set email alerts
|

Depression Suppresses Treatment Response for Traumatic Loss–Related Posttraumatic Stress Disorder in Active Duty Military Personnel

Abstract: There are multiple well-established evidence-based treatments for posttraumatic stress disorder (PTSD). However, recent clinical trials have shown that combat-related PTSD in military populations is less responsive to evidence-based treatments than PTSD in most civilian populations. Traumatic death of a close friend or colleague is a common deployment-related experience for active duty military personnel. When compared with research on trauma and PTSD in general, research on traumatic loss suggests that it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…A final point to discuss is the fact that PTSD in humans is considered as a failure to follow the normative trajectory of recovery (e.g., in terms of physiological, cognitive, or behavioral symptoms) after exposure to a traumatic event [148]. Recent evidence indicates that some individuals may take long periods of time to recover from PTSD [149] and, therefore, animal studies may need to define the range of testing that would allow characterizing deficiencies in remote symptoms, e.g., [150].…”
Section: Recoverymentioning
confidence: 99%
“…A final point to discuss is the fact that PTSD in humans is considered as a failure to follow the normative trajectory of recovery (e.g., in terms of physiological, cognitive, or behavioral symptoms) after exposure to a traumatic event [148]. Recent evidence indicates that some individuals may take long periods of time to recover from PTSD [149] and, therefore, animal studies may need to define the range of testing that would allow characterizing deficiencies in remote symptoms, e.g., [150].…”
Section: Recoverymentioning
confidence: 99%
“…Many PTSD treatment studies also measure depression symptoms, which tend to show moderate to large reductions that are maintained for longer periods posttreatment (Resick et al, 2015; Zoellner et al, 2019). For example, Jacoby et al (2019) showed that patients who “recovered less from depression recovered less from PTSD” (p. 780) in a military sample. Interestingly, depression level may interact with response to PTSD treatment (Kline et al, 2018), and PTSD and depression may show different long-term recovery trajectories in response to disorder-specific therapy treatments (Karyotaki et al, 2016; Kline et al, 2021).…”
Section: Purpose Of the Studymentioning
confidence: 99%